Exploring the Community-Based Adaptation Strategies :An Anthropological Study on Local Knowledge in Patharghata Upazila, Bangladesh - Mahabubur Rahaman, M d (South Asian Journal of Social Sciences and Humanities, 2023)
The geographical location, land characteristics, the multiplicity of rivers and the monsoon climate render Bangladesh highly vulnerable to natural hazards (Kabir & Hossen, 2019). The general economic situation and cultural way of life of Bangladesh's coastal residents have been impacted by climate change. The risk of natural disasters such as cyclones, storms, floods, and salinity are the greatest in Bangladesh's coastal regions (Chowdhury, 2007). In order to comprehend how the natural disasters brought on by climate change affect people's lives, the study has taken into account the fishing and farming communities of Patharghata, a coastal Upazila of the Barguna region. Both qualitative and quantitative (mix-method) approaches were used to reach the study's objectives. The first-hand data is collected using Case Study, KII, FGD, Semi-structured Interview, Structured Interview, and observation. This study has found some local strategies followed by the people to predict and adapt the natural calamities. The govt of Bangladesh and different NGOs and INGOs are working to mitigate the climate change challenges. The study demonstrates that these activities of government and NGOs have some weaknesses, so they sometimes fail to make positive changes at the root level. The local people have their own social, political, and religious belief system and worldview, which significantly impacts disaster response. To achieve the sustainable development goal of this area, it needs to apply bottom-up policy formulation synchronizing their local social context.
Keywords: Climate change; adaptation strategies; political ecology; Religious belief; Govt and NGOs policy